2003
DOI: 10.1007/s00436-002-0758-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyst burden in the brains of Wistar rats fed Toxoplasma oocysts

Abstract: Six strains of Toxoplasma oocysts were used to infect groups of 4-24 Wistar rats, with each rat being fed 10 1 -10 4 oocysts from a single strain. After 2 months, the rats were killed, their brains screened for Toxoplasma cysts and then bioassayed in mice if negative. Toxoplasma was either observed in the form of brain cysts or was recovered using the bioassay, from 113 out of 138 (82%) rat brains. As few as ten oocysts were capable of initiating a brain infection that lasted for at least 2 months in eight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…One possible explanation for the similarity of effect of spiramycin and pyrimethamine-sulphonamide on intracranial lesions could be that they both reduce the infective parasite burden. This burden, along with individual host resistance, route of infection and parasite strain, has been related to brain and ocular lesions in experimental animal studies [30,31]. If reduction of parasite burden is the mechanism, the timing of treatment might be critical, as conversion from tachyzoite to bradyzoite cyst, which is impenetrable to antibiotics, has been found to take place between 4 and 14 d after infection in immunecompetent experimental animals [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the similarity of effect of spiramycin and pyrimethamine-sulphonamide on intracranial lesions could be that they both reduce the infective parasite burden. This burden, along with individual host resistance, route of infection and parasite strain, has been related to brain and ocular lesions in experimental animal studies [30,31]. If reduction of parasite burden is the mechanism, the timing of treatment might be critical, as conversion from tachyzoite to bradyzoite cyst, which is impenetrable to antibiotics, has been found to take place between 4 and 14 d after infection in immunecompetent experimental animals [1].…”
Section: Discussionmentioning
confidence: 99%
“…If reduction of parasite burden is the mechanism, the timing of treatment might be critical, as conversion from tachyzoite to bradyzoite cyst, which is impenetrable to antibiotics, has been found to take place between 4 and 14 d after infection in immunecompetent experimental animals [1]. However, why treatment should have an effect on brain but not ocular lesions remains puzzling as experimental and human fetal studies of ocular toxoplasmosis have found that severe lesions are associated with a locally increased burden of free tachyzoite [31,32]. We were unable to explore the effect of prenatal treatment on long-term development of retinochoroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the similarity of effect of spiramycin and pyrimethamine‐sulphonamide on intracranial lesions could be that they both reduce the infective parasite burden. This burden, along with individual host resistance, route of infection and parasite strain, has been related to brain and ocular lesions in experimental animal studies 30, 31. If reduction of parasite burden is the mechanism, the timing of treatment might be critical, as conversion from tachyzoite to bradyzoite cyst, which is impenetrable to antibiotics, has been found to take place between 4 and 14 d after infection in immune‐competent experimental animals 1.…”
Section: Discussionmentioning
confidence: 99%
“…If reduction of parasite burden is the mechanism, the timing of treatment might be critical, as conversion from tachyzoite to bradyzoite cyst, which is impenetrable to antibiotics, has been found to take place between 4 and 14 d after infection in immune‐competent experimental animals 1. However, why treatment should have an effect on brain but not ocular lesions remains puzzling as experimental and human fetal studies of ocular toxoplasmosis have found that severe lesions are associated with a locally increased burden of free tachyzoite 31, 32. We were unable to explore the effect of prenatal treatment on long‐term development of retinochoroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, even after parasite clearance, the loss of fear phenotype is still observed in rodents [168]. It is more likely that cysts will secrete a substance that affects the innate fear pathway in the brain [94,169]. More importantly this model is unable to explain why other amygdala and nucleus accumbens dependent behaviours like conditioned fear, neophobia to novel food and social status remain intact [94,149] The Toxoplasma parasite has two genes that are analogous to the human tyrosine hydroxylase gene [92,[170][171][172].…”
Section: Toxoplasma Gondii-rattus Norvegicus Associationmentioning
confidence: 99%